Analisis Produksi, Distribusi Pendapatan Petani dan Dampak Program Optimalisasi Lahan Terhadap Produksi Padi Sawah di Kabupaten Muaro Jambi - Junaidi Junaidi; Zamzami Zamzami; Erni Achmad (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
The purposes of this study are ; ( 1 ) How does the social and economic characteristics of rice farmers in Jambi Muaro ; ( 2 ) What factors are affecting rice production in Muaro Jambi; ( 3 ) How is the impact of the land optimization program toward the increase of rice production in Muaro Jambi and ( 4 ) How is the income distribution of rice farmers in Muaro Jambi. The methodology of research used in this study is survey method using primary data and secondary data . Analysis tools used in this study are qualitative description and quantitative description using Cobb Douglas Production-Function Model , and the Gini Index Ratio . The findings in this study are ; ( 1 ) The Average production per hectare of rice farmers in the study area during the growing season was below the average production of Muaro Jambi district . ( 2 ) Over-All Test ( F Test ) showed that the land variable, orea fertilizer , seeds, labor capital , farming experience and education level have influenced the rice production . While based on the partial test, it was showed that only the land area variable ( X1 ) and orea fertilizer ( x2 ) which significantly influence rice production while the amount of seed variable ( X3 ) , labor ( X4 ) , capital ( X5 ) , experience ( D1 ) , and formal education ( D2 ) had no significant effect on rice production in the research area ' ( 3 ) The land optimization has increased the income of the farmers' compared to pre-optimization condition, but the gini index ratio is higher as a result of the maximization of income to farmers who have more land which is proven by The Gini Index Ratio: 0.30 in pre-optimization and after optimization of land it raises to 0:32 ; ( 4 ) The Land-Optimization Program which has implemented by the Government Muaro Jambi has positive impact both on increasing rice production and the income of farmers. Key words : Optimization of Land , Production Optimization , Gini Ratio